Tuesday, January 25, 2011

Square: Try it

Square: Try it We know that
(a+b)^2 = a^2 + 2ab + b^2.
With the help of above we can find out the square of a number in the following way…
(11)^2 = (1^2) (2×1×1) (1^2)
= (1) (2) (1)
=121.
(12)^2 = (1^2) (2×1×2) (2^2)
= (1) (4) (4)
= 144.
(13)^2 = (1^2) (2×1×3) (3^2)
= (1) (6) (9)
= 169.
(14)^2 = (1^2) (2 ×1×4) (4^2)
= (1) (8) (16)
= (1) (8+1) (6)
= (1) (9) (6)
= 196.
(15)^2 = (1^2) (2 ×1×5) (5^2)
= (1) (10) (25)
= (1+1) (0+2) (5)
= (2) (2) (5)
=225.
(16)^2 = (1^2) (2×1×6) (6^2)
= (1) (12) (36)
= (1+1) (2+3) (6)
= (2) (5) (6)
= 256.
(17)^2 = (1^2) (2×1×7) (7^2)
= (1) (14) (49)
= (1+1) (4+4) (9)
= (2) (8) (9)
= 289.
(18)^2 = (1^2) (2×1×8) (8^2)
= (1) (16) (64)
= (1+1) (6+6) (4)
= (2) (12) (4)
= (2+1) (2) (4)
= (3) (2) (4)
= 324
(19)^2 = (1^2) (2×1×9) (9^2)
= (1) (18) (81)
= (1+1) (8+8) (1)
= (2) (16) (1)
= (2+1) (6) (1)
= 361.
(20)^2 = (2^2) (2×2×0) (0^2)
= (4) (0) (0)
= 400.
(21)^2 = (2^2) (2×2×1) (1^2)
= (4) (4) (1)
= 441.
(25)^2 = (2^2) (2×2×5) (5^2)
= (4) (20) (25)
= (4+2) (0+2) (5)
= (6) (2) (5)
= 625.
(98)^2 = (9^2) (2×9×8) (8^2)
= (81) (144) (64)
= (81) (144+6) (4)
= (81) (150) (4)
= (81+15) (0) (4)
= (96) (0) (4)
= 9604.